2019
DOI: 10.3390/ijerph17010266
|View full text |Cite
|
Sign up to set email alerts
|

Local–Migrant Interaction in Everyday Life in an Ancient Tourism Town

Abstract: Daily interaction is a primary means of understanding social change which is of vital importance for community well-being. In tourism host communities, daily interactions among different resident groups reflect tourism’s effects which are directly related to tourists’ experiences and community harmony. In this exploratory article, grounded theory was applied to analyze daily interactions between locals and migrants in Zhouzhuang, the first ancient tourism town in China, based on in-depth interviews. A model fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The use of several methods to generate and analyse data further assisted with both methodological and data triangulation (Taswell et al 2019;Zhang et al 2019) as some sources of data needed double authentication. There was just too much information generated within very short periods.…”
Section: Methodology: Theories and Methods Utilisedmentioning
confidence: 99%
“…The use of several methods to generate and analyse data further assisted with both methodological and data triangulation (Taswell et al 2019;Zhang et al 2019) as some sources of data needed double authentication. There was just too much information generated within very short periods.…”
Section: Methodology: Theories and Methods Utilisedmentioning
confidence: 99%
“…Conversely, the perception of humanistic resources with uncertain historical value decreased. Some studies [66][67][68] have indicated that typical cultural and natural resources are the primary motivations for tourists to take a trip. People tend to travel when they encounter trouble or failure and want to escape from daily life for a short time period [69].…”
Section: Tourists' Perceived Characteristics Of Tourism Resources In ...mentioning
confidence: 99%
“…Although SNSs can help in keeping migrants close to their homelands, they can also hinder their motivation to establish new social relationships with local residents in destination countries, which may, in turn, affect their well-being (Zhang et al 2019;Lee et al 2020). A lack of motivation to engage in relationship building with local residents coupled with language and other barriers may result in the social loneliness of migrants despite having a sizeable social network, frequent contacts, and good family relationships (ten Kate et al 2020).…”
Section: Migration and Social Networking Servicesmentioning
confidence: 99%